Design of a digital beam attenuation system for computed tomography. Part II. Performance study and initial results. Issue 2 (16th January 2013) - Szczykutowicz, Timothy P.; Mistretta, Charles A.
Abstract : Purpose: : The purpose of this work is to present a performance study of the digital beam attenuator (DBA) for implementing fluence field modulated CT (FFMCT) using a simulation framework developed to model the incorporation of the DBA into an existing CT system. Additionally, initial results will be presented using a prototype DBA and the realization of the prototype will be described. To our knowledge, this study represents the first experimental use of a device capable of modulating x‐ray fluence as a function of fan angle using a CT geometry. Methods: : To realize FFMCT, the authors propose to use a wedge design in which one wedge is held stationary and another wedge is moved over the stationary wedge. Due to the wedge shape, the composite thickness of the two wedges changes as a function of the amount of overlap between the wedges. This design allows for the wedges to modulate the photon fluence incident onto a patient. Using a simulation environment, the effect of changing the number of wedges has on dose, scatter, detector dynamic range, and noise uniformity is explored. Experimental results are presented using a prototype DBA having ten Fe wedges and a c‐arm CT system geometry. The experimental DBA results are compared to non‐DBA scans using scatter and detector dynamic range as metrics. Both flat field and bowtie filtered CT acquisitions were simulated for comparison with the DBA. Results: : Numerical results suggest that substantial gains in noise uniformity and scatter‐to‐primary ratio (SPR) can be obtained using only seven wedges. After seven wedges, the decrease in noise ununiformity and SPR falls off at a lower rate. Simulations comparing CT acquisitions between flat field, bowtie enabled, and DBA CT acquisitions suggest DBA‐FFMCT can reduce dose relative to flat field CT by ≈3 times. A bowtie filter under the same imaging conditions was shown to only allow a dose reduction of 1.65 times. Experimentally, a 10 wedge DBA prototype result showed a SPR reduction of ≈4 times relative to flat field CT. The dynamic range for the DBA prototype was 3.7 compared to 84.2 for the flat field scan. Conclusions: : Based on the results presented in this paper and the companion paper [T. Szczykutowicz and C. Mistretta, "Design of a digital beam attenuation system for computed tomography. Part I. System design and simulation framework, " Med. Phys., (2013)]10.1118/1.4773879, FFMCT implemented via the DBA device seems feasible and should result in both a dose reduction and an improvement in image quality as judged by noise uniformity and scatter reduction. In addition, the dynamic range reduction achievable using the DBA may allow photon counting imaging to become a clinical reality. This study may allow for yet another step to be taken in the field of patient specific dose modulation.